Effects Of Safety-Specific Transformational Leadership, Safety Management Practices And High-Quality Relationships On Mindful Safety Practices In Petroleum Industry Of China - Hu, Shi (2021)
The main objective of this study is to investigate the impacts of safety-specific transformational leadership, safety management practices, and high-quality relationships on mindful safety practices of first line workers in the Chinese Petroleum Industry mediated by safety motivation. The Petroleum Industry as one of the traditional pillar industries has made great contributions to Chinese GDP growth and revenue. However, Petroleum Industry belongs to the high-risk industry, and potential hazards related to safety, health and environment exist. The conduction of mindful safety practices by first line workers in the Chinese Petroleum Industry facilitates safety promoting programs and excellent safety records in the workplace. In addition, two theories that are High Reliability Organization (HRO) theory and Leader Member Exchange (LMX) theory are adopted in this study. Among these two theories, HRO theory is regarded as the underpinning theory in this study. Moreover, in this study judgment sampling, which contains purposive sampling and non-probability sampling is applied for data collection of first line workers in a Chinese Petroleum Company. In total, 255 questionnaires are available with a response rate of 79.69%. PLS-SEM is adopted for data analysis and the examination of hypothesized relationships by SmartPLS software.